The Roles of Strategic Human Resource Management and Person–Environment Fit On Nonprofit Public Service Motivation. (2nd January 2021) - Kim, Min Young; Torneo, Ador
Abstract: This study examines the relationship between public service motivation (i.e., intrinsically and voluntarily driven attitudes and dispositions), strategic human resource management, and person–environment fit in Korean nonprofit organizations in order to determine the ways by which both the motivation of employees and the performance of these organizations can be enhanced. This was done using data from a survey on Korean nonprofit organizations employees conducted in 2013. The results show a direct, positive, and significant association between strategic human resource management and person–environment fit, a direct and positive association between person–environment fit and the affective and normative nonprofit public service motivation aspects of nonprofit public service motivation, and a mediating role of person–environment fit in the relationship between strategic human resource management and affective and normative nonprofit public service motivation.